A broadband cavity-backed slot spiral antenna. - Volakis, J.L (IEEE Antennas & propagation magazine.)
When compared to printed cavity-backed spirals, slot spiral antennas offer the possibility of designs that are conformal and very thin. We discuss the physical characteristics of a cavity-backed slot spiral, as well as the associated infinite balun and termination designs. Simulations of the proposed cavity-backed spiral are presented and used to optimize the antenna's various parameters. Comparisons of measurements and calculations are also given, to validate the gain and axial-ratio computations. Several options for miniaturizing this design, using capacitive and inductive loadings, are also presented